UJI EFEKTIFITAS SEDIAAN SPRAY GEL EKSTRAK BUNGA KENOP (Gomphrena globosa L) TERHADAP PENYEMBUHAN LUKA BAKAR - Irma Novrianti; Sari Wijayanti; Heriani Heriani (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2022)
A burn wound is tissue damage after contacting a heat source. Globe amaranth (Gomphrena globosa) is effective for healing burn wounds. This research analyzes the formula of spray gel pursuant to pharmaceutical requirements and the spray gel’s ability to heal burn wounds. The spray gel preparation was made from 12.5%, 15%, and 20% concentrations of globe amaranth extract. Based on the stability test, the spray gel of globe amaranth preparation is stable in storage The test of the effectiveness of globe amaranth-based gel spray for healing burn wounds was conducted on test animals divided into five groups, i.e., control positive (bioplasenton®), control negative (gel-base), FI (spray gel preparation at a 12.5% concentration of globe amaranth extract), FII (spray gel preparation at a 15% concentration of globe amaranth extract), and FIII (spray gel preparation at a 20% concentration of globe amaranth extract) and induced using an iron plate of diameter 1.5 cm. The results indicated a burn wound healing percentage of 51.33% (P%) on test animals on day 14. On FII, the P% was 62%, and FIII, the P% was 63.33% at p < 0.05. The percentage of burn wound healing on FII and FIII was the same as that on control positive at p > 0.05. To conclude, the spray gel preparation from globe amaranth extracts at 15% and 20% concentrations was effective for healing burn wounds.